The effect of tyres and a rubber track at high axle loads on soil compaction-Part 2: Multi-axle machine studies - Ansorge, Dirk; Godwin, R. J. (Elsevier, 2008)
This paper reports on a study of the effect of the passage of multi-axle harvesting machines on the soil physical properties. In particular, it investigates the effect of the rear tyre of a combine harvester on the amount of soil compaction subsequent to the passage of the front tyre/track. The work was conducted in controlled laboratory conditions to determine the effect of a simulated self-propelled combine harvester with a total machine weight of 30–33 t. This was assessed by embedding talcum powder tracer lines in the soil to measure soil displacement and soil density changes. Dry bulk density and penetrometer resistance were also measured. The results showed that the benefit of the rubber track found by Ansorge and Godwin [2007a. The effect of tyres and a rubber track at high axle loads on soil compaction: Part 1: Single Axle Studies. Biosystems Engineering 98 (1), 115–126] was maintained after the additional passage of the rear tyre. After the passage of a track the effect of rear tyre size was insignificant, but the rear tyre size had a significant influence on soil density when following a leading tyre. This was due to a higher strength layer at the soil surface created by the track which was able to withstand the load of the subsequent passes and protect the soil below from further compaction. Results similar to those found for a tracked machine were also achieved by three passes of a 900 mm section width tyre at 5 t load and 0.5 bar inflation pressure. The track results for the 33 t machine were very similar to those of a smaller combine harvester with a total load of 11 t and similar rut width. The study confirmed the benefit of tracks with regard to soil compaction and emphasised the fact that total axle loads and machine weights are less important than how the loads are distributed to the soil.